2017
DOI: 10.1039/c6tb03130g
|View full text |Cite
|
Sign up to set email alerts
|

A biomaterial approach to cell reprogramming and differentiation

Abstract: Cell reprogramming of somatic cells into pluripotent states and subsequent differentiation into certain phenotypes has helped progress regenerative medicine research and other medical applications. Recent research has used viral vectors to induce this reprogramming; however, limitations include low efficiency and safety concerns. In this review, we discuss how biomaterial methods offer potential avenues for either increasing viability and downstream applicability of viral methods, or providing a safer alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 111 publications
(134 reference statements)
1
18
0
Order By: Relevance
“…On the other hand, PEGDA hydrogels without RGD modifications or with caged RGD support few adherent cells and the cells have round morphology. Besides, it has been reported that RGD peptides can be introduced to polymers, such as HA (Lee et al, 2015 ), alginate (Sun et al, 2017 ), chitosan (Kim et al, 2016 ), and PEG (Long et al, 2017 ), by chemical binding to fabricated bioactive hydrogels. These functionalized hydrogels show improved biological properties to promote cell adhesion, spreading, proliferation, and differentiation.…”
Section: Control Of Chemical Propertiesmentioning
confidence: 99%
“…On the other hand, PEGDA hydrogels without RGD modifications or with caged RGD support few adherent cells and the cells have round morphology. Besides, it has been reported that RGD peptides can be introduced to polymers, such as HA (Lee et al, 2015 ), alginate (Sun et al, 2017 ), chitosan (Kim et al, 2016 ), and PEG (Long et al, 2017 ), by chemical binding to fabricated bioactive hydrogels. These functionalized hydrogels show improved biological properties to promote cell adhesion, spreading, proliferation, and differentiation.…”
Section: Control Of Chemical Propertiesmentioning
confidence: 99%
“…The technique was subsequently refined and developed by several research groups (e.g., [45,46,47,48,49]). Although avoiding the problem of IM, the efficiency of piPSC protocols is generally low (0.001–0.006%) [50], this being most likely due to failure of the proteins to penetrate the hydrophobic cell membrane [51]. The low cell permeability has been partly overcome through fusion of the proteins with cell penetrating peptides [44] or, more recently, by treatment of the donor cells with titanium oxide nanotubes [52], and use of bolaamphiphiles to stabilize cell membrane proteins and so facilitate uptake of the proteins [53].…”
Section: Reprogramming Leads To Genetic Dysregulationmentioning
confidence: 99%
“…Hydrogels of hyaluronic acid give further examples of the extraordinary influence on ESC and PSC proliferation and differentiation Poly-L-lactic acid (PLLA)/poly-glycolic acid (PLGA), Matrigel, each possesses the capacity to choreograph cartilage, endothelial tubules, neurons, and hepatocytes. [27][28][29] Innovative solutions to the problem focus on the spatial and temporal separation of the defining factors in cell transformations. [30] Precisely targeting the individual cell with transcription factors, functional gene sequences, small proteins, and chemically defined small molecules is a prominent role for dynamic, information-rich biological materials and their structures.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels of hyaluronic acid give further examples of the extraordinary influence on ESC and PSC proliferation and differentiation Poly‐L‐lactic acid (PLLA)/poly‐glycolic acid (PLGA), Matrigel, each possesses the capacity to choreograph cartilage, endothelial tubules, neurons, and hepatocytes. [ 27–29 ]…”
Section: Introductionmentioning
confidence: 99%